Enhancing the Intense Field Control of Molecular Fragmentation - Anis, Fatima; Esry, B. D. (My University, 2012)
We describe a pump-probe scheme with which the spatial asymmetry of dissociating molecular fragments—as controlled by the carrier-envelope phase of an intense few-cycle laser pulse—can be enhanced by an order of magnitude or more. We illustrate the scheme using extensive, full-dimensional calculations for dissociation of H+2 and include the averaging necessary for comparison with experiment.